Effectiveness of bioactive combinations of several plant substances to inhibit the growth of Escherichia coli and Salmonella sp. - T. Pasaribu; A. P. Sinurat; E. Wina; T. Purwadaria; T. Haryati; I.W. R. Susana (Indonesian Center for Animal Research and Development (ICARD), 2018)
The use of antibiotic growth promoters (AGP) has been banned as feed additives in many countries, therefore the alternatives need to be found. An in vitro experiment was conducted to study the potential of combination of some plant extract to inhibit growth of pathogen bateria that normally occur in the poultry gastro intestinal tract.The combination of three plants bioactives (liquid smoke of cashew shells of Anacardium occidentaleor CLS, Phyllanthus niruri L. extract (EM), and Synzygium aromaticum extract (EDC) were formulated and evaluated for its effectiveness to inhibit growth of Escherichia coli and Salmonella sp. in vitro.The mixtures (KE) were then made in 3 different concentrations, i.e. 100 % KE, 50% KE, and 25% KE and studied their effectiveness to inhibit growth of E. coli or Salmonella sp. using microplate reader method. The results showed that the higher the concentration of the bioactive combination (KE100) the higher the ability to inhibit the growth of E. coli or Salmonella sp. The combination of bioactive substances CAM, EM, and EDC more effectively than Zn-bacitracin antibiotics to inhibit the growth of E. coli and Salmonella sp. The optimum concentration of KE with the similar effectiveness as the AGP was 25%. It was concluded that the combination of CAM, EM, and EDC was able to inhibit the growth of E. coli and even capable to eliminate the presence of Salmonella sp. In the biological assay, a combination of CAM, EM, and EDC either extract or powder form, high dose, medium or low does not affect the weight of the spleen, bursa fabricius, and blood profile. The best combination of CAM, EM, and EDC extracts to decreases the total bacterial population and E. coli was middle dose ie 0.0625% (extract) and 0.625% (powder). Likewise for live weight gain that was a good dose of extract or powder form can replace antibiotics. It was concluded that combinations of CAM, EM, and EDC had potential as a substitute for AGP in poultry feed, especially chickens.